KEMAMPUAN NUMERASI SISWA MENYELESAIKAN SOAL HOTS PADA MATERI POSISI GARIS TERHADAP LINGKARAN - Muhammad Hakim Setiawan; Riski Amelia; Rahmatya Nurmeidina (Universitas Muhammadiyah Lampung, 2023)
This research is a Quantitative Descriptive research that aims to describe how the numeracy skills of Global Islamic Boarding School students in solving HOTS level math problems. The problems given were 3 problems. The research subjects were NS B1 XI class students as many as 9 people. Numeracy skills focus on the ability of students to analyze, give reasons and convey ideas effectively, formulate, solve, and interpret problems in various forms and this can be seen in working on HOTS level problems. The results of this study are for question number 1, the average for the first indicator is 1.33, then the second indicator has an average of 1.22, and the third indicator has an average of 1.22. For question 2, the average on the first indicator is 0.89, then on the second indicator has an average of 0.67, and on the 3rd indicator has an average of 0.33. And for the 3rd question, the average on the first indicator is 0.44, then on the second indicator has an average of 0.55, and on the 3rd indicator has an average of 0.33. The conclusion from these three questions is that the lowest numeracy ability of students in class XI NS B1 in working on HOTS questions given is their ability to interpret the results of the analysis to predict, formulate, and make decisions, it is because most of the students of XI NS B1 have not been able to interpret the results of the analysis of the questions given to predict and make decisions correctly.